Política e educação na ciência social de Karl Marx - Luciano José Gonçalves Moreira (2024)
This thesis intends to present specific characteristics of the Politics category and the Education category in Karl Marx's social theory, as important elements in the revolutionary formation of the Social Being so that it can overcome capitalist society and constitute Human Emancipation. Karl Marx (1818-1883) is one of the most influential thinkers in the history of social theory. His ideas about class struggle, alienation, surplus value, and historical materialism provided a crucial basis for understanding social, economic, and political dynamics. The Social Being, based on the environment in which he lives, is formed (Education) according to the society that surrounds him and, therefore, his relationships and interactions are established within the framework of this social circle (Politics). In capitalism, people are formed by the values inherent to this system and, only through a social revolution, which takes into account the categories of Politics and Education, would they be able to modify living conditions, enabling Human Emancipation. This process was investigated from “On the Jewish Question” (1843), “Critique of Hegel's Philosophy of Law” (1844), “Critique of Hegel's Philosophy of Law - Introduction” (1844), “Critical Gloss marginal to the article 'The King of Prussia and social reform': from a Prussian” (1844), “Economic-philosophical Manuscripts” (1844) and “Criticism of the Gotha Program” (1875), for presenting discussions that dealt with the categories which are the objects of investigation in this thesis. The development of research on Marx's work is outlined by an immanent reading and analysis approach, crucial to understanding his ideas about life and the world. This method requires a direct understanding of the object of study, without external influences, and is essential for a faithful investigation. The initial chapter focuses on two key points: the understanding of materialism and objectivity, essential to understanding what Marx analyzed, and immanent reading as a research method, remaining faithful to the author's work. Although Marx did not leave a specific method, his approach emphasized the apprehension of concrete reality, without getting lost in conjecture. The thesis then seeks to apply the immanent reading to Marx's works, aiming to understand and reflect on their content without deviating from what was said by the author. In chapter 2, the research delves deeper into the ontology of the social being present in Marx's works, highlighting the importance of Work and its relationship with other human dimensions. The writing delves into Marx's early works, exploring themes such as Work, Politics, Human Formation, Education and Emancipation, seeking to understand the underlying social theory. In chapters 3 and 4, Politics and Education are discussed as fundamental Emancipation processes for Human Formation and for overcoming social inequalities. The conclusion, in the last chapter, demarcates the categories, object of study, as present and essential categories in the Marxian perspective, highlighting their relationship with Work and its influence on other areas of the life of the Social Being. Thus, enabling criticism of capitalist society and the consequent awareness of the social revolution and the construction of a new society based on liberating and human foundations.